Utilization of silica fume and clamshell ash as stabilization materials for kaolin clay - Syaza Syamiera, Jamhuri; Muzamir, Hasan; Nik Noor Atyrah, Nik Aziz (Penerbit Universiti Teknologi Malaysia, 2025)
Soil stabilization, particularly through chemical methods involving the incorporation of binders such as cement, ground granulated blast furnace slag, silica fume, lime, fly ash, and bottom ash is a highly successful and extensively employed method for improving the characteristics of problematic soils. Clay soils are one of the problematic soils that are unsuitable for construction due to their low bearing capacity, significant settlement, compression, and high-water content. The focus of the study was to determine the physical properties of the materials used (kaolin clay, SF and CSA) and the strength of kaolin clay mixed with optimal SF and various percentages of CSA. In this research, kaolin soil was treated with a Silica Fume (SF) and Clamshell Ash (CSA) blend in order of 2, 4, and 6% of SF and 3, 6, and 9% of CSA by dry weight of soil. The molded specimens were cured for 30, 60, 90, and 120 days. The mixing sample was carried out under Unconfined Compression Test to determine the maximum undrained shear strength when mixed with optimal percentage of SF and (3, 6 and 9%) of CSA content. Furthermore, the outcomes of the unconfined compressive strength test demonstrated a substantial enhancement in the soil's strength, increasing by up to 93.71%, from 189.75 kN/m² to 253.43 kN/m², by inclusion of 6% silica fume and 9% clamshell ash after 120 days of curing. Thus, SF and CSA can be utilized for stabilizing soft soils.